Characteristics of dry eye syndrome in patients with subclinical and manifest hypothyroidism - G.I. Drozhzhyna; M.I. Pavlovskii (Ukrainian Society of Ophthalmologists, 2017)
Background. The most common pathology of the thyroid gland is hypothyroidism. The decreased level of thyroid hormones in the body leads to development of hypothyroidism and is accompanied by metabolic, functional, and structural changes in different body organs and tissues including the eye. Thyroid gland disorders are known to be associated with the risk of development of dry eye syndrome (DES). However, the characteristics of the clinical course of DES in subclinical and manifest hypothyroidism remain almost unstudied. The purpose of the present paper was to reveal clinical characteristics of dry eye syndrome in patients with subclinical and manifest hypothyroidism. Material and Methods. A total of 87 patients (174 eyes) with primary hypothyroidism, aged 19 to 78 (М=50.5 SD12.5), were studied. The patients were diagnosed primary hypothyroidism by an endocrinologist and had dry eye syndrome. All the patients were recorded with Lvov Regional Clinical Diagnostic and Treatment Endocrinologic Center. Of them, there were 72 (82.8%) women and 15 (17.2%) men. Severity of DES was assessed according to DEWS classification (2007) that included patients' self-assessment of severity and frequency of subjective symptoms. Tear film break up time (TFBUT), tear production (Schirmer I) test, biomicroscopy of the anterior eye, and fluoroscein staining were also performed. Results. The patients with subclinical hypothyroidism were more often revealed to have clinical symptoms and objective signs of DES corresponding to stage I and II of the syndrome while the symptoms and clinical signs corresponding to DES stage III were more common in manifest hypothyroidism. The most differences were noted in such signs as discomfort in the eye, conjunctival staining and the presence of inclusions in the tear film. A summed value of tear production was 9.4 (SD5.9) mm in subclinical hypothyroidism while that was significantly lower, in manifest hypothyroidism, 6.1 (SD5.4) mm, (р=0.0002). Stability of tear film was also lower in manifest than in subclinical hypothyroidism, 5.04 (SD2.0) and 5.84 (SD2.2) s, respectively, (р=0.0110). DES stage III was 5 significantly more often revealed in manifest hypothyroidism as compared to the subclinical type, 20 patients (54.1%) and 5 patients (10.0%), respectively, (?2 = 20, 22, р=0.00004). Conclusions. Tear production disorders are revealed both in subclinical and manifest hypothyroidism. In manifest hypothyroidism, the disorders are more apparent, which is evidenced by a decrease in tear production functional samples and a higher incidence of the severe stage of DES. In this regard, the hypothyroidism patients require ophthalmologist's examination and follow up for an adequate tear substitute therapy to be prescribed and keratopathy development to be prevented.